Correlation of serum TSH levels with serum ferritin levels in children of β thalassemia major presenting at tertiary care hospital - Shoaib, Faghia; Saeed, Rabia; Khan, Sara; Siddiqa, Ayesha; Bashir, Sibgha; Safdar, Shoaib (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To study the correlation of serum TSH levels with serum ferritin levels in children of β thalassemia major presenting at tertiary care hospital. Material and methods: Between April 2020 and October 2020 total 88 patients of β thalassemia major having age 5-15 years either male or female were selected from Department of Pathology, Sheikh Zaid Hospital, Rahim Yar Khan. Correlation of between ferritin and TSH levels was studies. Results: Mean age was 8.02 ± 2.792 years, mean TSH level was 3.9564 ± 2.38263 µIU/ml, mean ferritin level was 3282.84 ± 1782.013 ng/dl and mean duration of blood transfusion was 3.23 ± 1.328 years. (Table 1) Out of 88 patients, 67 (76%) were males and 21 (24%) were females. TSH levels was negatively correlated with ferritin levels which was not significant (r = -0.073, P= 0.496). Conclusion: In this study negative correlation was detected between ferritin and TSH levels. Difference of mean ferritin and TSH level among both gender, age group was detected.